2021
DOI: 10.1080/10643389.2021.1974256
|View full text |Cite
|
Sign up to set email alerts
|

Pore characteristics of hydrochars and their role as a vector for soil bacteria: A critical review of engineering options

Abstract: Hydrothermal carbonization (HTC) is the method of choice to convert wet waste biomass to hydrochars. Their porous structure can serve as a microenvironment to plantgrowth-promoting rhizobacteria (PGPR), supporting their growth, survival, and activities. As published work lacks the systematic compilation of pore characteristics of hydrochars related to bacterial colonization, we collect available data and elaborate on their dependence on the carbonization process conditions, feedstocks, and methodology of pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…This led to the formation of empty spaces within the material, as the porogen evaporated during the calcination process [19,21]. In this study, the HA material synthe- Building upon the information provided, HAP samples modified with porogens yield materials with structure, morphologies, porosities, and physicochemical properties capable of creating a conducive environment for the growth of living organisms, facilitating the delivery of diverse biological molecules, and serving bone tissue engineering applications [24,26,45]. Nevertheless, achieving precise control and optimal alignment between porosity and physicochemical properties needs to be carried out for more specialized applications.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the formation of empty spaces within the material, as the porogen evaporated during the calcination process [19,21]. In this study, the HA material synthe- Building upon the information provided, HAP samples modified with porogens yield materials with structure, morphologies, porosities, and physicochemical properties capable of creating a conducive environment for the growth of living organisms, facilitating the delivery of diverse biological molecules, and serving bone tissue engineering applications [24,26,45]. Nevertheless, achieving precise control and optimal alignment between porosity and physicochemical properties needs to be carried out for more specialized applications.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, hydrochar application in soil has also been shown to enhance nitrogen immobilization with reduced activity of both nitrification and denitrification processess (Wang et al, 2015). Due to the presence of dissolved organic carbon (DOC), the labile form of carbon serves as a easily accessible carbon source for the microbial communities (Thunshirn et al, 2021). It has been shown that hydrochar addition can promote the activity of microbial communities involved DOC decomposition ( Flavobacterium, Anaerolinea, Penicillium, and Acremonium ) while negatively impacting the activity of the microorganisms involved in polycyclic aromatic hydrocarbon (PAH) degradation ( Sphingobacterium ) (Sun et al, 2020).…”
Section: Nutrient‐rich Hydrochar Application In Soilmentioning
confidence: 99%
“…Although PGPR has emerged as a sustainable and efficient approach to enhancing saline–alkali soil, its application in agriculture is often constrained by factors such as an unstable survival mode in the soil, diminished survival rate, and duration, consequently leading to reduced efficacy of bacteria . Liu et al introduced PSB either alone or in combination with fertilizer into tomato cultivation, resulting in a significant enhancement of the tomato yield and increased availability of phosphorus.…”
Section: Introductionmentioning
confidence: 99%